Peningkatan motivasi belajar siswa melalui project “globalisasi” dalam pembelajaran IPS - Riza Despita; Maria Montesori (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2019)
This research aims to improve students ‘ learning motivation on Globalization held at class IX. 7 MTs N 1 Bukittinggi through Learning Project-Based Learning model with the method of efficiency of mapping the Mind. This Research Study shaped the action classes that researchers do two cycles, each cycle four times. Each cycle comprises planning, action, execution, and reflection. The subject of research grade IX. 7 years Lessons 2018/2019. The data source through the student and teacher. The technique of collecting data through observation and question form. Data analysis with descriptive with calculated the percentage. Quantitative data used (assessment of learning results) qualitative data (now motivate learning). The results showed the EXECUTION model using the method of Mind efficiency of mapping content globalization class IX. 7 years 2018/2019 lessons can improve student learning motivation on the cycle, I 80% increased to 85% in cycle II. With increasing student learning outcomes learning motivation can also be increased from 50.00% in cycle, I became 83.33% in cycle II.